2003
DOI: 10.1161/01.str.0000063141.24491.50
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Triflusal and Aspirin for Prevention of Vascular Events in Patients After Cerebral Infarction

Abstract: MD; for the TACIP InvestigatorsBackground and Purpose-The efficacy of the antiplatelet agent triflusal for prevention of vascular events after stroke has been reported in a pilot study. However, there is a need to confirm those results in a larger study. Methods-We performed a randomized, double-blind, multicenter study to test the efficacy of triflusal (600 mg/d) versus aspirin (325 mg/d) for prevention of vascular events in patients with stroke or transient ischemic attack (Triflusal versus Aspirin in Cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 43 publications
2
79
1
4
Order By: Relevance
“…Moreover, patients treated with triflusal had a lower risk of hemorrhage than those treated with ASA (14,15,42,46). Triflusal was associated with significantly fewer episodes of cerebral hemorrhage (0.3% in patients treated with triflusal vs. 1.0% in patients treated with ASA), and the reduction was also evident in patients who received fibrinolytic therapy (14).…”
Section: Adverse Reactionsmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, patients treated with triflusal had a lower risk of hemorrhage than those treated with ASA (14,15,42,46). Triflusal was associated with significantly fewer episodes of cerebral hemorrhage (0.3% in patients treated with triflusal vs. 1.0% in patients treated with ASA), and the reduction was also evident in patients who received fibrinolytic therapy (14).…”
Section: Adverse Reactionsmentioning
confidence: 96%
“…In long-term studies the efficacy of triflusal was similar to that of ASA, but the former led to fewer bleeding complications (see below) (15,42). Triflusal can be, therefore, considered the antiplatelet drug of choice or an alternative to ASA.…”
Section: Secondary Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 ), a multicentric pilot study, including 431 patients, and Triflusal Aspirin Cerebral Infarction Prevention (TACIP) (ref. 41 ), including 2113 patients. In both studies, the effect of TRIF 600 mg a day and ASA 325 mg a day was compared.…”
Section: Triflusalmentioning
confidence: 99%
“…However, a significant decrease in total incidence of extra-and intracranial hemorrhages was observed in the TACIP study (16.4% in TRIF vs. 24.5% in ASA) (ref. 41 ). Similar findings were also observed in the TAPIRSS study -no differences were found in the primary endpoint that combined the incidence of vascular death, cerebral ischemic infarction, nonfatal MI, or major hemorrhage (13.9% in ASA vs. 12.7% in TRIF).…”
Section: Triflusalmentioning
confidence: 99%